2017
DOI: 10.7150/jca.21368
|View full text |Cite
|
Sign up to set email alerts
|

DNA Methylation Analysis of the SHOX2 and RASSF1A Panel in Bronchoalveolar Lavage Fluid for Lung Cancer Diagnosis

Abstract: Introduction: Currently the majority of lung cancer patients are diagnosed as advanced diseases for no sensitive and specific biomarkers exist, noninvasive biomarkers with high sensitivity and specificity are urgently needed in lung cancer diagnosis. Bronchoscopy is a standard procedure of the diagnostic work-up of patients with suspected lung cancer despite of the limited diagnostic accuracy. Besides, epigenetic changes through DNA methylation play an important role in tumorigenesis. Thus, we examined the abe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
59
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(66 citation statements)
references
References 22 publications
5
59
2
Order By: Relevance
“…While cytology analysis is typically performed on bronchoalveolar lavage (Carvalho et al, 2017) there is also opportunity to use the lavage fluid for liquid biopsy. Methylated SHOX2 and RASSF1A gene promoters were detected in lavage fluid from 322 patients with a sensitivity of 81% for lung cancer detection (Zhang et al, 2017). Other studies have also revealed high sensitivity for lung cancer detection using bronchoalveolar lavage fluid, with 75% and 78% for PCDHGA12 (Jeong et al, 2018) and SHOX2 (Dietrich et al, 2012) methylated DNA, respectively.…”
Section: Designing An Effective Assaymentioning
confidence: 99%
“…While cytology analysis is typically performed on bronchoalveolar lavage (Carvalho et al, 2017) there is also opportunity to use the lavage fluid for liquid biopsy. Methylated SHOX2 and RASSF1A gene promoters were detected in lavage fluid from 322 patients with a sensitivity of 81% for lung cancer detection (Zhang et al, 2017). Other studies have also revealed high sensitivity for lung cancer detection using bronchoalveolar lavage fluid, with 75% and 78% for PCDHGA12 (Jeong et al, 2018) and SHOX2 (Dietrich et al, 2012) methylated DNA, respectively.…”
Section: Designing An Effective Assaymentioning
confidence: 99%
“…DNA hypermethylation is an important event in carcinogenesis that can be detected in plasma-derived cell-free DNA, which makes it an ideal and useful biomarker for early detection and staging of cancer. Many studies have demonstrated that DNA methylation analysis of specific genes can be used for the early diagnosis of cancer, such as plasma mSEPT9 in colorectal cancer [ 19 ], bronchoalveolar lavage fluid SHOX2 and RASSF1A in lung cancer, [ 20 ], and urine GSTP1 in prostate cancer [ 21 ]. However, there is no FDA-approved circulating epigenetic biomarker that has been shown to be useful to diagnose HCC.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, detection of ctDNA methylation can be used for early tumor diagnosis and assessment of prognosis, as it can reflect tumor load changes [ 43 , 44 ]. The most widely used lung cancer-specific gene methylation detection kit is the human SHOX2 and RASSF1A gene methylation DNA detection kit [ 45 ], which could assist in the early diagnosis of lung cancer and in the differentiation between benign and malignant pulmonary nodules. Additionally, together with a cytological test, it can effectively improve the sensitivity and specificity of lung cancer detection.…”
Section: Revolutionary Changes Brought By Liquid Biopsy Technologymentioning
confidence: 99%